2010
DOI: 10.1039/c0cp00551g
|View full text |Cite
|
Sign up to set email alerts
|

Observation of two-step nucleation in methane hydrates

Abstract: In this work we show that homogeneous nucleation of methane hydrate can, under appropriate conditions, be a very rapid process, achieved within tens of nanoseconds. In agreement with recent experimental results on different systems, we find that the nucleation of a gas hydrate crystal appears as a two-step process. It starts with the formation of disordered solid-like structures, which will then spontaneously evolve to more recognizable crystalline forms. This previously elusive first-stage state is confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
343
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(375 citation statements)
references
References 31 publications
31
343
1
Order By: Relevance
“…The classical nucleation theory that assumes the spontaneous appearance of a fully ordered nucleus has been questioned and a two-stage mechanism has been suggested. Starting with the formation of an intermediate ordered state, referred to liquid-like clusters, the second step involves the structural evolution to the regular crystalline form [50,51].…”
Section: Product Designmentioning
confidence: 99%
“…The classical nucleation theory that assumes the spontaneous appearance of a fully ordered nucleus has been questioned and a two-stage mechanism has been suggested. Starting with the formation of an intermediate ordered state, referred to liquid-like clusters, the second step involves the structural evolution to the regular crystalline form [50,51].…”
Section: Product Designmentioning
confidence: 99%
“…[19][20][21] Theoretically, the nucleation and growth process of methane hydrate have been simulated and explored on the atomic and molecular level through molecular dynamics simulations. [23][24][25][26][27][28][29][30] The interaction between host water cages and guest molecules, 32,41 stability, diffusion and vibrations of guest molecules in water cavities of clathrate hydrates, 31,34,[38][39][40][42][43] and phase transition between ice and methane clathrates have been studied by firstprinciple calculations. 37,44 Experimentally, Raman spectra of hydrocarbon hydrates have demonstrated that the CH stretching frequency of the guest molecule is commonly (but not always) lower when in a large cage than when in a small cage [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] The nucleation, growth, and dissociation process has been investigated by MD simulations in the last few years. [32][33][34][35][36][37][38] In the quantum-chemical investigations most focus has been on the interaction between host and guest molecules, [39][40] stability and diffusion of guest molecules in water cavities of clathrate hydrates, [41][42][43][44] and phase transitions. [45][46] Liu et al evaluated the performance of twenty density functional theory (DFT) methods for the description of the intermolecular interaction in methane hydrates.…”
Section: Introductionmentioning
confidence: 99%